FLORISTIC ANALYSIS IN A TOPOSEQUENCE OF THE MUNICIPALITY OF SERRINHA DOS PINTOS-STATE OF RIO GRANDE DO NORTE - Queiroz, Francisco Jiliardo de; Medeiros, Jacimária Fonseca de; Queiroz, Rubens Teixeira de (Ra'e Ga: o Espaço Geográfico em Análise, 2021)
Aiming to contribute to the knowledge of the vegetation of the municipality of Serrinha dos Pintos, state of Rio Grande do Norte, a floristic analysis was carried out along a toposequence. Three distinct areas were selected: Chapada (700 m to 720 m altitude), Encosta (410 m to 510 m altitude) and Depressão (270 m to 310 m altitude), with allocation of 30 fixed plots of 10 mx 10 m, 10 plots in each area. All individuals with heights greater than or equal to 1 meter and circumference greater than 10 centimeters were sampled. In order to observe the richness and diversity of the study areas, the Shannon-Wiener Diversity Index (H’) was calculated. In all, 821 individuals were collected, identified in 35 species and 19 families. Chapada was the area with the highest diversity of species (21), the families Fabaceae (8 spp.) and Euphorbiaceae (3 spp.) were the most representative; (18 spp.), Encosta had (18 spp.), also Fabaceae (8 spp.) and Euphorbiaceae (3 spp.) were the families with the highest richness and Depressão was the area with the lowest diversity (14 spp.), including Fabaceae (5 spp.) and Euphorbiaceae (3 spp). The most representative species in the three areas were Croton blanchetianus (Marmeleiro), Cenostigma bracteosum (caatingueira) and Myracrodruon urundeuva (Aroeira). The Shannon-Wiener diversity index (H’) observed for the Chapada area was 2.42, in Encosta, it was 2.07 and in Depressão, it was 1.91. It is emphasized that the greater the result, the greater the diversity of species in the area in question.